EXPLORING EFL STUDENTS’ PRACTICE ON ANNOTATION AS READING STRATEGY - Mardiah, Radiatan; Melati, Melati (Universitas Negeri Malang, 2023)
Annotating is an active reading strategy for improving comprehension and retention of information. However, it is not always clear how the EFL learner understand and use it. The purpose of this paper is to explore students practice on annotation as their reading strategy. The participants are a class of EFL students enrolled in Reading and Writing for Academic Purposes in a public university in Jambi, Indonesia. The data were collected through the students’ written reflection and classroom discussion. The qualitative analyses on the data revealed that the students have adequate understanding about annotation, and they use it to achieve their reading goals. However, some of them stated that they lack practice, and their annotating skills are insufficient. Therefore, ample time and effort for practicing the strategy are needed to help students in their learning.